Always my grandpa a story for children about Alzheimer's disease - Scacco, Linda; Wong, Nicole E. (Washington, D.C. Magination Press, 2006)
During a summer at his grandfather's house, young Daniel, with his mother's help, begins to understand Alzheimer's disease and how it affects not only Grandpa, but the entire family, as well.
Ages 6-10.
Keywords: Alzheimer's disease -- Fiction; Grandfathers -- Fiction; Old age -- Fiction; Mothers and sons -- Fiction; Storytelling -- Fiction